Influence of the duration of breastfeeding on quality of muscle function during mastication in preschoolers: a cohort study - Pires Simone; Giugliani Elsa Regina; Caramez da Silva Fernanda (BMC, 2012)
Abstract Background There is some evidence of the benefits of breastfeeding to masticatory function, but no studies have evaluated the influence of breastfeeding duration on the quality of this function. The objective of this study was to investigate the association between duration of breastfeeding and quality of masticatory function in preschoolers. Methods Cross-sectional study nested in a contemporary cohort of 144 randomly selected Brazilian infants. Data on sociodemographic, dietary, and sucking-related parameters were collected shortly after birth and at 7, 30, 60, 120, and 180 days of life. Masticatory function was assessed between the ages of 3 and 5 years, using a standardized procedure involving three foodstuffs of different consistencies, for evaluation of incision, lip competence, masticatory patterns, masticatory movements, and perioral muscle use. The quality of masticatory function was scored, and multiple linear regression was used to test for association between this score and the duration of breastfeeding. Results A positive correlation was found between duration of breastfeeding and masticatory function scores (rs = 0.473; p < 0.001). Children breastfed for at least 12 months had significantly higher average scores, regardless of bottle-feeding or pacifier use. Children who were breastfed for longer were more likely to score satisfactorily across all tested parameters. Conclusions Breastfeeding has a positive impact on mastication. In our sample, duration of breastfeeding was positively associated with the quality of masticatory function at preschool age.